Assessment of Guardian Peach Rootstock for Resistance to Two Isolates of Pratylenchus vulnus - Nyczepir, A. P. (Society of Nematologists, 2001)
Guardian, Lovell, and Nemaguard peach rootstocks were evaluated for their susceptibility and growth response to two isolates of Pratylenchus vulnus. One nematode isolate was obtained from peach in Georgia (P. vulnus [GA-isolate]) and the other from apple in Idaho (P. vulnus [ID-isolate]). Nematode reproduction and pathogenicity as related to rootstock were determined 29 months after inoculation in outdoor microplots. All rootstocks were susceptible to both nematode isolates. Guardian supported a greater number of nematodes per gram dry root weight than Lovell or Nemaguard rootstocks. All rootstocks supported greater numbers of P. vulnus (GA-isolate) than P. vulnus (ID-isolate). Tree growth among the three rootstocks was similar in the presence of either P. vulnus isolate, but growth suppression was greatest in P. vulnus (GA-isolate) plots, intermediate in P. vulnus (ID-isolate) plots, and least in the uninoculated plots.